ChemInform Abstract: Epoxidation of Alkenes Through Oxygen Activation over a Bifunctional CuO/Al2O3 Catalyst. Issue 25 (3rd June 2013) - Scotti, Nicola; Ravasio, Nicoletta; Zaccheria, Federica; Psaro, Rinaldo; Evangelisti, Claudio
Abstract A CuO/Al2O3 catalyst is shown to be highly effective for the one‐pot epoxidation of olefins, such as (I), (III), and (V) using cumene as solvent and oxygen carrier.